How Can Business Success Affected By Entrepreneurial Competence? - Ramadhani, Ulfha; Mulyadi, Hari (Journal of International Conference Proceedings, 2023)
Entrepreneurial competence plays a crucial role in the success of business endeavors. Effectively managing a business requires essential abilities and skills from entrepreneurs, which are crucial for achieving efficiency and ultimately reaching a state of success. The quality of entrepreneurial competence also has a positive impact on the performance of small and medium enterprises (SMEs), especially during economic crises. This study aims to investigate the influence of entrepreneurial competence on business success, focusing on three dimensions: strategic, commitment, & organizing. The research conducted is descriptive and verification in nature. The study involved 113 groups of female farmers involved in ground coffee production in West Lampung. Two stages of testing were conducted, including validity and reliability tests, and path analysis was employed for data analysis. The findings of the study indicate that the dimensions of entrepreneurial competence significantly influence business success.